A double-network gradient polysaccharide-based self-lubricating hydrogel coating and its preparation method and application
By depositing dopamine/multivalent metal ion bridge layer on medical implant materials and forming a dual network gradient hydrogel coating, the problem of implantable materials in the prior art failure in vivo is solved, and the matching of high mechanical strength and excellent lubricating performance is achieved.
Patent Information
- Application Number
- CN202310702850.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-06-14
AI Technical Summary
The prior art is difficult to achieve compression modulus and biolubricating properties matching biological tissues on medical implant materials, resulting in the failure of the material when in vivo service.
A dual-network gradient polysaccharide self-lubricating hydrogel coating is designed, and a hydrophobic association structure is formed by depositing a dopamine/multival metal ion bridge layer on the surface of the target modified material substrate, and a blended solution of sodium alginate or sodium carboxymethylcellulose and polyvinyl alcohol is used to form a gradient crosslinked physical network, and a hydrophobic association structure is formed in combination with surfactant to achieve self-lubricating effect.
The high mechanical strength and excellent lubricating properties of the hydrogel coating are achieved, with a friction coefficient of up to 9.1×10-4 and a compression modulus up to 15.8MPa, matching the mechanical properties and tribological properties of biological tissues.
Smart Images

Figure CN116688241B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material surface modification, and in particular to a double-network gradient polysaccharide-based self-lubricating hydrogel coating and a preparation method and application thereof. Background Art
[0002] Implanting medical materials is the only way to maintain the function of damaged biological tissues that cannot heal themselves in clinical practice. However, due to the high modulus of the implant body and the weak lubrication surface, the implanted materials are prone to bone resorption or foreign body sensation in the body. At the same time, the weak lubrication surface induces an inflammatory response, which eventually leads to the failure of the material when it is in service in the body. In order to enhance the compatibility of materials with tissues, the surface of the material needs to be modified to match the modulus of biological tissues or enhance the lubrication effect.
[0003] Hydrogels have high water content and mechanical properties similar to the modulus of soft tissue. Therefore, in recent years, hydrogels can be used as surface modification materials to form coatings to avoid direct contact between hard material substrates and soft tissues. However, the promotion and application of hydrogels are limited by: (1) high swelling properties sacrifice some strength; (2) the surface friction coefficient cannot meet the requirements of biological lubrication (10 -3 ~10 -4 ); (3) Low adhesion to the modified substrate, resulting in the risk of peeling.
[0004] Taking polyvinyl alcohol (PVA) or polysaccharide-based hydrogels with stable chemical properties and low biological toxicity as an example, their compression modulus is about 10 1 ~10 2 kPa, under complex working conditions such as high load and reciprocating sliding, the single gel network breaks and the defect expansion will directly lead to macroscopic cracks in the gel and even fragments. In addition, the low modulus hydrogel cannot match the modulus of the hard substrate, and the bonding point with the substrate is prone to asynchronous deformation rate due to the huge difference in modulus, which amplifies the shear and tensile stress of the contact surface and increases the risk of coating peeling.
[0005] The friction coefficient of polyvinyl alcohol or polysaccharide-based hydrogels is usually 10 -1 ~10 -2 , which is far less than the friction coefficient in biolubrication (10 -3 ~10 -4 ). In order to improve the lubrication performance of the gel surface, highly hydrophilic polymers such as polypyrrolidone and polyacrylamide can be introduced into the hydrogel to reduce the interfacial friction. However, the lubrication effect of the hydrogel is still far from the real biological lubrication, especially the boundary water lubrication at low sliding rate. And if the compression modulus of the gel is simply increased to meet the mechanical strength requirements of the hydrogel, the friction coefficient will be further reduced.
[0006] The invention patent application document with the publication number CN 115400264 A discloses a method for preparing a ceramic artificial joint grinding pair, firstly, a metal-doped porous zirconia toughened alumina (Me-ZTA) ceramic is prepared by a rapid hot pressing sintering method, then the surface is modified by dopamine hydrochloride (DA) to obtain a PDA-Me-ZTA artificial joint grinding pair, and then polyvinyl alcohol (PVA) and polydopamine (PDA) are used as raw materials to prepare a polydopamine (PDA)-polyvinyl alcohol (PVA) composite hydrogel coating on the surface of the PDA-Me-ZTA artificial joint grinding pair ceramic to construct a bionic articular cartilage material. The invention improves the lubrication and wear resistance of ceramic joints, reduces the incidence of complications such as wear, rupture, and abnormal noise in the clinical application of ceramic joints, and improves the quality of ceramic joints and patient comfort.
[0007] The invention patent application document with publication number CN 104150787 A discloses a modification method for preparing a highly hydrophilic coating by a dopamine-induced sol-gel method. The invention comprises dissolving dopamine in an alkaline aqueous solution, adding an ethanol solution containing tetraethyl orthosilicate, and preparing an impregnation solution; immersing a solid material to be modified in the impregnation solution, and washing the taken-out solid material with anhydrous ethanol and deionized water in turn to complete the highly hydrophilic modification of the solid material.
[0008] Although there have been reports on the modification of gelation coatings on the surface of substrates by dopamine, how to make the hydrogel coating have a compression modulus close to that of both high-strength substrates and soft biological tissues, that is, the hydrogel needs to have a gradient compression modulus, and the surface friction coefficient of the hydrogel coating needs to match that of biological lubrication, has not yet been well solved at home and abroad.
[0009] Therefore, it is necessary to design a double physically cross-linked hydrogel, with the help of dopamine coating and multivalent metal ions, to simultaneously achieve the adhesion and gradient physical cross-linking of the hydrogel coating, and to cooperate with the hydrophobic association structure formed by surfactants to construct a hydrogel coating with a biological lubrication effect on the surface and a high supporting capacity in the body, so as to solve the problems existing in the above-mentioned prior art. Summary of the invention
[0010] In order to solve the above technical problems, the present invention provides a method for preparing a double-network gradient polysaccharide-based self-lubricating hydrogel coating. The method is easy to implement and has mild reaction conditions. It can simultaneously improve the mechanical strength and self-lubricating friction properties of the physically cross-linked hydrogel coating. The prepared hydrogel has excellent mechanical strength and lubrication properties.
[0011] A method for preparing a double-network gradient polysaccharide-based self-lubricating hydrogel coating comprises the following steps:
[0012] (1) adding a first polymer, a second polymer, and a surfactant into deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution, wherein the first polymer is sodium alginate or sodium carboxymethyl cellulose, and the second polymer is polyvinyl alcohol;
[0013] (2) Immersing the target modified material substrate in a Tris solution containing dopamine hydrochloride / polyvalent metal ions, depositing a polydopamine / polyvalent metal ion bridging layer on the surface of the target modified material substrate, and obtaining a substrate-PDA / M n+ Modified material, wherein PDA is polydopamine, M n+ For polyvalent metal ions; the substrate is rinsed with deionized water -PDA / M n+ The uncrosslinked dopamine monomers and the multivalent metal ions not complexed by the bridging layer are removed from the surface of the modified material;
[0014] (3) Covering the hydrogel coating mixed precursor solution obtained in step (1) with the substrate-PDA / M obtained in step (2) n+ Modified material surface, the polymer chains in the hydrogel coating mixed precursor solution and PDA adhere to the substrate-PDA / M through non-covalent bonds n+ Modified material surface, M n+ Diffusion from the bridging layer into the mixed precursor solution of the hydrogel coating, complexation and crosslinking with the first polymer, to obtain a hydrogel coating of a gradient crosslinked first physical crosslinked hydrogel network;
[0015] (4) The hydrogel coating of the gradient cross-linked first physically cross-linked hydrogel network obtained in step (3) is subjected to cyclic freeze-thaw cycles, and the polyvinyl alcohol bound in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The free metal ions are removed by soaking until the hydrogel size is stable, thereby obtaining a double-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0016] The method of the present invention deposits a polydopamine / multivalent metal ion bridging layer on the surface of the target modified material substrate, wherein the PDA plays a role in bonding the polymer in the hydrogel to the surface of the target modified material substrate. n+ Diffusion from the bridging layer to the mixed precursor solution of the hydrogel coating, the precursor solution contains a first polymer sodium alginate or sodium carboxymethyl cellulose, a second polymer polyvinyl alcohol, and a surfactant. n+ Physical cross-linking of sodium alginate or sodium carboxymethyl cellulose is achieved by complexation to construct a cross-linking density that varies with M. n+The first gradient physical cross-linked network with a continuously decreasing diffusion direction, the precursor solution undergoes a sol-gel transition, and the shape of the hydrogel coating is fixed so that the subsequent freeze-thaw cycle can form a second physical cross-linked network of polyvinyl alcohol (PVA). The second network formed by physical crystallization of polyvinyl alcohol can enhance the mechanical strength of the gel body. Finally, the hydrogel coating forms a physical double network gel with a high cross-linking density near the surface of the target modified material substrate. The high cross-linking density produces a high compression modulus to play a load-bearing role; the physical double network gel with a low cross-linking density is formed away from the surface of the target modified material substrate. The low cross-linking density produces a low compression modulus gel. The surfactant is different from the relaxation formation of the gel network skeleton, which promotes the reduction of the surface friction coefficient of the hydrogel and produces a self-lubricating effect.
[0017] Preferably, in step (1), the weight average molecular weight of the sodium alginate is 30,000 to 250,000, and the ratio of β-D-mannuronic acid to α-L-guluronic acid is 0.5 to 1.5; the weight average molecular weight of the sodium carboxymethyl cellulose is 3,000 to 3,000,000, and the degree of substitution is 0.5 to 0.9.
[0018] The weight average molecular weight of sodium alginate and sodium carboxymethyl cellulose should not be too low. Polymers with low weight average molecular weight are difficult to construct a complete three-dimensional network skeleton, and the resulting gel has low mechanical strength and poor mechanical properties and cannot bear high stress. An excessively high weight average molecular weight significantly enhances the chain entanglement effect, causing the viscosity of the hydrogel coating mixed precursor solution to increase. In the subsequent process of covering the substrate surface, the gel pre-solution is not only unable to degas due to the high viscosity, but also significantly increases the coating thickness, causing uneven coating coverage.
[0019] Preferably, in step (1), the degree of polymerization of the polyvinyl alcohol is 1,000 to 5,000, and the degree of alcoholysis is 85 to 99%.
[0020] The degree of polymerization of polyvinyl alcohol should not be too low. Polyvinyl alcohol with low weight average molecular weight cannot form a second physical cross-linked gel network through freeze-thaw cycles due to its short polymer chain. Polyvinyl alcohol with high weight average molecular weight has too high a weight average molecular weight, which enhances the chain entanglement effect, causes the viscosity of the mixed precursor solution of the hydrogel coating to increase, and increases the difficulty in the coating process. The degree of alcoholysis of polyvinyl alcohol should not be too low. The second physical cross-linked network in the hydrogel coating relies on the crystalline regions formed by the hydroxyl groups on the polyvinyl alcohol polymer chains to produce cross-links. If the alcoholysis degree is too low, the hydroxyl density is low, and sufficient crystalline regions cannot be formed, which weakens the strength of the second physical cross-linked network.
[0021] Preferably, in step (1), based on the mass of the hydrogel coating mixed precursor solution, the mass fraction of the first polymer is 1-5%, the mass fraction of the second polymer is 5-20%, and the mass ratio of the first polymer to the second polymer is 1:1-10.
[0022] If the amount of sodium alginate or sodium carboxymethyl cellulose and polyvinyl alcohol is too small, it is difficult to form a high-density network structure after the polymer chain swells, and it is even more difficult to form a perfect gradient network by complexing and crosslinking with the metal ions diffused from the bridging layer, and it is also impossible to form a second physical crosslinked gel network with a suitable crosslinking density through freeze-thaw cycles. Therefore, the low amount of polymer in the mixed precursor solution of the hydrogel coating cannot synergistically form a double network structure, and it is difficult to play a high-strength supporting role, and it is impossible to exert the excellent mechanical properties of the gel matrix. However, if the amount of sodium alginate or sodium carboxymethyl cellulose or polyvinyl alcohol is too large, on the one hand, the zero shear viscosity of the mixed solution is significantly increased, which makes it difficult to cast the gel, thereby introducing more bubbles in the gel matrix. On the other hand, when the multivalent metal ions in the bridging layer diffuse into the sol for complexing and crosslinking, there are too many sites for crosslinking with the sodium alginate or sodium carboxymethyl cellulose polymer chains at the beginning, and the crosslinking density is too high. A dense multi-network gel film is formed in the part where the gel first contacts the metal salt ions, which hinders the further diffusion of metal ions and is not conducive to the construction of the internal gradient network of the gel.
[0023] Preferably, in step (1), the surfactant is a nonionic surfactant or an ionic surfactant.
[0024] The present invention introduces a surfactant into a blended solution of sodium alginate or sodium carboxymethyl cellulose and polyvinyl alcohol, and the surfactant forms a site with low surface tension on the surface of the hydrogel, providing an extremely low friction coefficient, which is conducive to the application of the product hydrogel in the surface modification of medical implant materials. The hydrophilic part of the surfactant can form hydrogen bond interactions with the carboxylate in sodium alginate and sodium carboxymethyl cellulose, or with the hydroxyl in polyvinyl alcohol, and the hydrophobic part of the surfactant is exposed to the surface of the hydrogel, which reduces the surface tension of the gel. The free energy of the hydrophobic part is higher than that of the three-dimensional network skeleton of the gel, and the molecular relaxation behavior under sliding shear is significantly different from that of the gel body, thereby reducing the friction of the double network gradient structure physical cross-linked hydrogel, providing excellent lubricating properties, and giving the gel a self-lubricating effect.
[0025] Preferably, the nonionic surfactant includes long-chain fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine, polyoxyethylene alkylolamide or polyether surfactant. More preferably, the nonionic surfactant is sorbitan oleate, sorbitan monolaurate polyoxyethylene (20) ether or polyoxyethylene sorbitan fatty acid ester.
[0026] Preferably, the ionic surfactant includes fatty acid salt, alkyl sulfonate, alkylbenzene sulfonate, amino acid salt, carboxylic acid betaine, sulfobetaine, phosphate betaine or imidazoline surfactant. More preferably, the ionic surfactant is dodecyl dimethyl hydroxypropyl phosphate betaine, octadecyl hydroxypropyl sulfobetaine, sodium cocoyl carboxymethyl imidazoline acetate, sodium dodecyl sulfate or sodium dodecylbenzene sulfonate.
[0027] Preferably, in step (1), based on the mass of the hydrogel coating mixed precursor solution, the mass fraction of the surfactant is 0.1-8.0%, and the mass ratio of the surfactant to polyvinyl alcohol is 1:1-50.
[0028] If the amount of surfactant used is too small, not only will it fail to provide sufficient lubrication effect, but it will also produce steric hindrance due to the adsorption and aggregation between the surfactant and the polymer chain, occupying too many polymer chains and multivalent metal ion complexing sites, reducing the cross-linking density of the physical cross-linking network; if the amount of surfactant used is too large, it will also cause a large number of micelles to remain, increasing the risk of release from the gel body during later use, causing damage to the organism.
[0029] Preferably, in step (2), the target modified material substrate is a stainless steel material, a plastic material or a glass material.
[0030] Preferably, in step (2), the polyvalent metal ion is Ni 2+ 、Co 2+ , Cu 2+ Cr 3+ 、Zn 2+ 、Cd 2+ , Mn 2+ Mg 2+ , Ca 2+ , Fe 3+ 、Al 3+ , Ga 3+ 、Au 3+ or In 3+ .
[0031] Multivalent metal ions can replace sodium ions in sodium alginate or sodium carboxymethyl cellulose, and form a network structure with polymer chains through the complexation effect of multivalent metals.
[0032] Preferably, in step (2), the concentration of dopamine hydrochloride in the Tris solution is 2 to 15 mg / mL, the pH of the Tris solution is 8 to 11, and the molar concentration of the polyvalent metal ions in the Tris solution is 0.1 to 5 M.
[0033] The concentration of dopamine hydrochloride should not be too low, otherwise the density of the ortho-phenol structure on the surface of the polydopamine (PDA) layer formed by oxidation is low, and it cannot play the mediating role of the adhesion between the surface of the target modified material substrate and the hydrogel coating. However, the concentration of dopamine hydrochloride should not be too high. The polydopamine layer also has a complexing effect on polyvalent metal ions. Excessive dopamine hydrochloride will bind the polyvalent metal ions and prevent them from smoothly diffusing into the interior of the sol to construct a gradient cross-linked network structure.
[0034] The Tris solution with a pH of 8 to 11 is alkaline. The dopamine hydrochloride monomer is first oxidized to benzoquinone in an alkaline environment, then forms a trimer, and finally aggregates to form a polydopamine layer through hydrogen bond interaction and π-π stacking. However, the pH of the Tris solution should not be too high, otherwise the polyvalent metal ions are prone to precipitation.
[0035] Multivalent metal ions (M n+ ) concentration is too low to effectively realize complexation with the first polymer in the sol to construct a perfect gradient first network. n+ The concentration is too high. When the precursor solution contacts the bridge layer for a short time, M n+ A large amount of cross-linking occurs with the polymer chains of sodium alginate or sodium carboxymethyl cellulose, and the cross-linking density is too high, forming a dense network gel membrane in the part where the gel first contacts the metal salt ions, which hinders the further diffusion of metal ions and is not conducive to the construction of the gradient network inside the gel.
[0036] Preferably, in step (2), the immersion time is 5 to 48 hours.
[0037] If the immersion time is too short, the degree of oxidation of dopamine hydrochloride is low, and a complete dopamine bridging layer cannot be deposited on the surface of the target modified material substrate, which is not conducive to the subsequent adhesion of the hydrogel coating and the diffusion and complexation of metal ions; when the immersion time is greater than the time required for the complete oxidation of dopamine hydrochloride, extending the immersion time has no contribution to the perfection of the bridging layer.
[0038] The present invention deposits a polydopamine / multivalent metal ion bridging layer on the surface of a target modified material substrate during medical implantation. The bridging layer ensures the simultaneous construction of the hydrogel coating adhesion and the gradient cross-linking of the first physical cross-linking network: the gradient network formed by the diffusion of sodium alginate or sodium carboxymethyl cellulose through the ion diffusion in the bridging layer plays a role in fixing the original size of the gel and maintaining a low modulus on the gel surface and a high modulus inside the gel.
[0039] Preferably, in step (3), the hydrogel coating mixed precursor solution is covered on the substrate-PDA / M by dipping-pulling, scraping or spraying. n+ Modified material surface.
[0040] Preferably, in step (3), the diffusion temperature is 4 to 40° C. and the time is 1 to 48 hours.
[0041] If the diffusion temperature is too low, the diffusion rate of polyvalent metal ions will slow down and the efficiency of building the first gradient network will decrease. If the diffusion temperature is too high, the diffusion rate of polyvalent metal ions and molecular motion will increase significantly, the gradient structure of the first physical cross-linking network will weaken, and the mechanical strength of the formed hydrogel coating will not be significantly different, which is not conducive to improving the self-lubricating properties of the gel.
[0042] Diffusion time is too short, M n+ If the complexation time with the first polymer is too short, it is difficult to form an effective gradient structure first cross-linked network, which is not conducive to the realization of differentiated mechanical modulus of the hydrogel coating, and the coating cannot play the role of bearing mechanical properties. If the diffusion time is too long, the multivalent metal ions have been completely complexed, and the extension of time has no additional contribution to network construction.
[0043] Preferably, in step (4), the freezing temperature of the freeze-thaw cycle is -50 to -4°C, the thawing temperature is 4 to 40°C, and the number of cycles is 2 to 6 times.
[0044] The compression modulus of the hydrogel coating increases with the increase of the number of cycles of freezing and melting. When the number of cycles of freezing and melting increases, the ability to form inter-chain and intra-chain hydrogen bond condensation entanglement in the composite gel is enhanced, the stability between the crystals is also significantly improved, the network structure of the gel is more compact, the network gap within the unit volume is reduced, and the hole structure is reduced, thereby causing the compression strength of the gel to increase with the increase of the number of cycles of freezing and melting, so the number of freeze-melt cycles in the present invention is selected from 2 to 6 times.
[0045] Preferably, in step (4), the immersion condition is: immersion in water for 1 to 3 weeks, during which the water is changed several times until a dimensional stable equilibrium state of the hydrogel is reached.
[0046] The present invention also provides a double-network gradient polysaccharide-based self-lubricating hydrogel coating prepared by the above preparation method. The double-network gradient polysaccharide-based self-lubricating hydrogel coating of the present invention has high bearing capacity, low modulus surface and excellent lubrication performance.
[0047] The present invention also provides the application of the dual-network gradient polysaccharide-based self-lubricating hydrogel coating in the field of medical implant materials. The dual-network gradient polysaccharide-based self-lubricating hydrogel coating of the present invention has excellent mechanical strength and lubrication properties, and the friction coefficient can be as low as 9.1×10 -4 The compression modulus can reach up to 15.8MPa, which is similar to the mechanical and tribological properties of biological tissues, and has good application prospects in the field of medical implant materials.
[0048] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0049] (1) The method of the present invention is easy to implement, has mild reaction conditions, low cost, good safety, and is convenient for large-scale production.
[0050] (2) The present invention uses polydopamine / polyvalent metal ions (PDA / M n+ ) The bridging layer acts as an intermediary between the gel and the surface of the target modified material substrate. The hydrogel coating forms a tight adhesion with the surface of the target modified material substrate with the help of the PDA bridge. At the same time, the PDA / M n+ The multivalent metal ions in the bridging layer diffuse from the bridging layer into the mixed precursor solution of the hydrogel coating, and complex and cross-link with the first polymer sodium alginate or sodium carboxymethyl cellulose to form a first gradient physical cross-linked hydrogel network, followed by a freeze-thaw cycle of the second polymer polyvinyl alcohol to form a second physical cross-linked network. The double network gradient structure enables the hydrogel coating to have excellent mechanical bearing capacity, and the direct introduction of the surfactant into the mixed precursor solution of the hydrogel coating enables the gel coating to have a self-lubricating effect.
[0051] (3) The double-network gradient polysaccharide-based self-lubricating hydrogel coating prepared by the method of the present invention can be used as a stainless steel surface modification material, and the friction coefficient can be as low as 9.1×10 -4 The compression modulus can reach up to 15.8MPa, which is similar to the mechanical and tribological properties of biological tissues, and has good application prospects in the field of medical implant materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The figure is a schematic diagram of the preparation process of the double-network gradient polysaccharide-based self-lubricating hydrogel coating of the present invention.
[0053] Figure 2 Actual photograph of the double-network gradient polysaccharide-based self-lubricating hydrogel coating prepared in Example 1. DETAILED DESCRIPTION
[0054] The present invention will be further described below in conjunction with the embodiments and drawings. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0055] Example 1
[0056] (1) adding 1.0 wt % of a first polymer sodium alginate having a weight average molecular weight of 30,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 0.5, 8.0 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 1,000 and a degree of alcoholysis of 99%, and 8.0 wt % of a surfactant polyoxyethylene alkylamine to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0057] (2) The stainless steel plate was immersed in a solution containing 2 mg / mL dopamine hydrochloride and 0.1 M Ni2+ The solution pH was adjusted to 8 and the immersion time was 48 h. Polydopamine / Ni was deposited on the surface of the stainless steel plate. 2+ Bridge layer to obtain substrate-PDA / Ni 2+ , and then rinse the substrate-PDA / Ni with deionized water 2+ Surface removal of uncrosslinked dopamine monomers and Ni not complexed by the bridging layer 2+ ;
[0058] (3) The hydrogel coating mixed precursor solution in step (1) is dipped and pulled to cover the substrate-PDA / Ni in step (2) 2+ On the surface, PDA and the polymer chains in the precursor solution of the hydrogel coating undergo non-covalent interactions, adhering the polymer chains to the substrate surface. 2+ Ni in the bridging layer 2+ The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 48 h and the diffusion temperature is 24 °C. 2+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0059] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -50°C and the thawing temperature being 4°C, and the cycle is repeated twice. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then soaked for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0060] The double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this example has a water content of 92.9% and a compression modulus of 8.5 MPa. Figure 2 As shown. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 “Friction of Gels.4. Friction on Charged Gels” was adopted. Based on the steady-state friction test mode, under the conditions of load of 14 kPa, sliding rate of 0.001 mm / s and ambient temperature of 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface was only 2.3×10 -3In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.04 MPa and the friction coefficient was 1.5×10 -1 .
[0061] Example 2
[0062] (1) adding 1.5 wt % of a first polymer sodium alginate having a weight average molecular weight of 100,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 0.8, 6.0 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 1,500 and a degree of alcoholysis of 95%, and 3.0 wt % of a surfactant sorbitan oleate to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0063] (2) The glass plate was immersed in a solution containing 3.5 mg / mL dopamine hydrochloride, 0.3 M Cu 2+ The pH of the solution was adjusted to 8 and the immersion time was 44 h. Polydopamine / Cu 2+ Bridge layer to obtain substrate-PDA / Cu 2+ , and then rinse the substrate-PDA / Cu with deionized water 2+ Surface removal of uncrosslinked dopamine monomers and Cu that is not complexed by the bridging layer 2+ ;
[0064] (3) The hydrogel coating mixed precursor solution in step (1) is coated on the substrate-PDA / Cu in step (2) by scraping 2+ On the surface, PDA interacts non-covalently with the polymer chains in the precursor solution of the hydrogel coating, adhering the polymer chains to the substrate surface. 2+ Cu in the bridging layer 2+ The diffusion from the bridging layer to the mixed precursor solution of the hydrogel coating was carried out for 39 h at a diffusion temperature of 20 °C. 2+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0065] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -48°C and the thawing temperature being 4°C, and the cycles are repeated twice. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then soaked for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0066] The water content of the double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this embodiment is 74.1%, and the compression modulus is 7.2 MPa. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the journal Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 "Friction of Gels.4.Friction on Charged Gels", based on the steady-state friction test mode, when the load is 14 kPa, the sliding rate is 0.001 mm / s, and the ambient temperature is 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 9.1×10 -4 In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.32 MPa and the friction coefficient was 7.6×10 -1 .
[0067] Example 3
[0068] (1) adding 1.8 wt % of a first polymer sodium alginate having a weight average molecular weight of 150,000 and a ratio of β-D-mannuronic acid / α-L-guluronic acid of 1, 10 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 2,500 and a degree of alcoholysis of 90%, and 2.0 wt % of a surfactant sorbitan oleate to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0069] (2) The glass plate was immersed in a solution containing 5 mg / mL dopamine hydrochloride, 1 M Zn 2+ The pH of the solution was adjusted to 8.5, and the immersion time was 40 h. Polydopamine / Zn 2+ Bridge layer to obtain substrate-PDA / Zn 2+ , and then rinse the substrate-PDA / Zn with deionized water 2+ Surface removal of uncrosslinked dopamine monomers and Zn not complexed by the bridging layer 2+ ;
[0070] (3) Spraying the hydrogel coating mixed precursor solution in step (1) onto the substrate-PDA / Zn in step (2) 2+ On the surface, PDA and the polymer chains in the precursor solution of the hydrogel coating undergo non-covalent interactions, adhering the polymer chains to the substrate surface. 2+ Zn in the bridging layer 2+The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 35 h and the diffusion temperature is 16 °C. 2+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0071] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -36°C and the thawing temperature being 10°C, and the cycles are repeated twice. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then immersed for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0072] The water content of the double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this embodiment is 92.9%, and the compression modulus is 8.4 MPa. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the journal Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 "Friction of Gels.4.Friction on Charged Gels", based on the steady-state friction test mode, when the load is 14 kPa, the sliding rate is 0.001 mm / s, and the ambient temperature is 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 9.2×10 -4 In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.97 MPa and the friction coefficient was 8.1×10 -2 .
[0073] Example 4
[0074] (1) adding 2.0 wt % of a first polymer sodium alginate having a weight average molecular weight of 200,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 1.3, 20 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 4,000 and a degree of alcoholysis of 88%, and 2.0 wt % of a surfactant sorbitan monolaurate polyoxyethylene (20) ether to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0075] (2) The polyvinyl chloride plastic plate was immersed in a solution containing 6 mg / mL dopamine hydrochloride, 1.7 M Mn 2+The pH of the solution was adjusted to 8.5, and the immersion time was 36 h. Polydopamine / Mn was deposited on the surface of the polyvinyl chloride plastic plate. 2+ Bridge layer to obtain substrate-PDA / Mn 2+ , and then rinse the substrate-PDA / Mn with deionized water 2+ Surface removal of uncrosslinked dopamine monomers and Mn not complexed by the bridging layer 2+ ;
[0076] (3) The hydrogel coating mixed precursor solution in step (1) is dipped and pulled to cover the substrate-PDA / Mn in step (2) 2+ On the surface, PDA interacts non-covalently with the polymer chains in the precursor solution of the hydrogel coating, adhering the polymer chains to the substrate surface. 2+ Mn in the bridging layer 2+ The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 32 h and the diffusion temperature is 4 °C. 2+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0077] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -36°C and the thawing temperature being 12°C, and the cycles are repeated three times. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then immersed for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0078] The water content of the double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this embodiment is 76.2%, and the compression modulus is 10.9 MPa. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the journal Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 "Friction of Gels.4.Friction on Charged Gels", based on the steady-state friction test mode, when the load is 14 kPa, the sliding rate is 0.001 mm / s, and the ambient temperature is 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 7.1×10 -3In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.6 MPa and the friction coefficient was 2.8×10 -1 .
[0079] Example 5
[0080] (1) adding 2.5 wt % of a first polymer sodium alginate having a weight average molecular weight of 250,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 1.5, 15 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 5,000 and a degree of alcoholysis of 85%, and 0.5 wt % of a surfactant polyoxyethylene sorbitan fatty acid ester to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0081] (2) The stainless steel plate was immersed in a solution containing 8.7 mg / mL dopamine hydrochloride, 2.2 M Mg 2+ The solution pH was adjusted to 8.5, and the immersion time was 28 h. Polydopamine / Mg was deposited on the surface of the stainless steel plate. 2+ Bridge layer to obtain substrate-PDA / Mg 2+ , and then rinse the substrate-PDA / Mg with deionized water 2+ Surface removal of uncrosslinked dopamine monomers and Mg not complexed by the bridging layer 2 + ;
[0082] (3) The hydrogel coating mixed precursor solution in step (1) is coated on the substrate-PDA / Mg in step (2) by scraping 2+ On the surface, PDA and the polymer chains in the precursor solution of the hydrogel coating undergo non-covalent interactions, adhering the polymer chains to the substrate surface. 2+ Mg in the bridging layer 2+ The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 28 h and the diffusion temperature is 35 °C. 2+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0083] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -27°C and the thawing temperature being 16°C, and the cycles are repeated three times. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then immersed for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0084] The water content of the double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this embodiment is 91.7%, and the compression modulus is 8.08 MPa. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the journal Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 "Friction of Gels.4.Friction on Charged Gels", based on the steady-state friction test mode, when the load is 14 kPa, the sliding rate is 0.001 mm / s, and the ambient temperature is 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 5.6×10 -3 In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.98 MPa and the friction coefficient was 9.5×10 -2 .
[0085] Example 6
[0086] (1) adding 3.0 wt % of a first polymer sodium carboxymethyl cellulose having a weight average molecular weight of 3,000 and a degree of substitution of 0.9, 16 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 1,800 and a degree of alcoholysis of 94%, and 8.0 wt % of a surfactant dodecyl dimethyl hydroxypropyl phosphate betaine to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0087] (2) The polyethylene plate was immersed in a solution containing 10 mg / mL dopamine hydrochloride and 2M Ca 2+ The solution pH was adjusted to 9 and the immersion time was 24 h. Polydopamine / Ca was deposited on the surface of the polyethylene plate. 2+ Bridge layer to obtain substrate-PDA / Ca 2+ , and then rinse the substrate-PDA / Ca with deionized water 2+ Surface removal of uncrosslinked dopamine monomers and Ca2+ not complexed by the bridging layer 2+ ;
[0088] (3) Spraying the hydrogel coating mixed precursor solution in step (1) onto the substrate-PDA / Ca in step (2) 2+ On the surface, PDA interacts non-covalently with the polymer chains in the precursor solution of the hydrogel coating, adhering the polymer chains to the substrate surface. 2+ Ca in the bridging layer 2+ The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 24 h and the diffusion temperature is 40 °C. 2+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0089] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -27°C and the thawing temperature being 16°C, and the cycles are repeated three times. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then immersed for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0090] The double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this embodiment has a water content of 90.0% and a compression modulus of 15.8 MPa. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the journal Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 “Friction of Gels.4.Friction on Charged Gels”, based on the steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding rate of 0.001 mm / s, and an ambient temperature of 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 7.1×10 -3 In comparison, under the same conditions as other preparation processes, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and the surfactant was 0.6 MPa and the friction coefficient was 0.57.
[0091] Example 7
[0092] (1) adding 4.0 wt % of a first polymer sodium carboxymethyl cellulose having a weight average molecular weight of 90,000 and a degree of substitution of 0.7, 13 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 2,200 and a degree of alcoholysis of 87%, and 0.5 wt % of a surfactant octadecyl hydroxypropyl sulfobetaine to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0093] (2) The polyethylene terephthalate plate was immersed in a solution containing 11 mg / mL dopamine hydrochloride and 2.9 MFe 3+ The solution pH was adjusted to 9 and the immersion time was 16 h. Polydopamine / Fe was deposited on the surface of the polyethylene terephthalate plate. 3+ Bridge layer to obtain substrate-PDA / Fe 3+ , and then rinse the substrate-PDA / Fe with deionized water 3+ Surface removal of uncrosslinked dopamine monomers and Fe2+ not complexed by the bridging layer 3+ ;
[0094] (3) The hydrogel coating mixed precursor solution in step (1) is dipped and pulled to cover the substrate-PDA / Fe in step (2) 3+ On the surface, PDA interacts non-covalently with the polymer chains in the precursor solution of the hydrogel coating, adhering the polymer chains to the substrate surface. 3+ Fe in the bridging layer 3+ The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 18 h and the diffusion temperature is 8 °C. 3+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0095] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -24°C and the thawing temperature being 20°C, and the cycle is repeated 4 times. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then immersed for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0096] The water content of the double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this embodiment is 73.8%, and the compression modulus is 7.04 MPa. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the journal Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 "Friction of Gels.4.Friction on Charged Gels", based on the steady-state friction test mode, when the load is 14 kPa, the sliding rate is 0.001 mm / s, and the ambient temperature is 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 4.7×10 -3 In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.12 MPa and the friction coefficient was 7.0×10 -1 .
[0097] Example 8
[0098] (1) adding 4.5 wt % of a first polymer sodium carboxymethyl cellulose having a weight average molecular weight of 500,000 and a degree of substitution of 0.5, 6.0 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 3,500 and a degree of alcoholysis of 88%, and 0.3 wt % of a surfactant sodium coconut carboxymethyl imidazoline acetate to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0099] (2) The glass plate was immersed in a solution containing 13 mg / mL dopamine hydrochloride, 3.6 M Al 3+ The solution pH was adjusted to 10 and the immersion time was 12 h. Polydopamine / Al was deposited on the glass surface. 3+ Bridge layer to obtain substrate-PDA / Al 3+ , and then rinse the substrate-PDA / Al with deionized water 3+ Surface removal of uncrosslinked dopamine monomers and Al2O3 not complexed by the bridging layer 3+ ;
[0100] (3) The hydrogel coating mixed precursor solution in step (1) is coated on the substrate-PDA / Al in step (2) by scraping 3+ On the surface, PDA interacts non-covalently with the polymer chains in the precursor solution of the hydrogel coating, adhering the polymer chains to the substrate surface. 3+ Al in the bridging layer 3+The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 16 h and the diffusion temperature is 6 °C. 3+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0101] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -20°C and the thawing temperature being 25°C, and the cycle is repeated four times. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then immersed for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0102] In this embodiment, the water content of the prepared double network gradient polysaccharide-based self-lubricating hydrogel coating is 83.7%, and the compression modulus is 7.7 MPa. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the journal Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 "Friction of Gels.4.Friction on Charged Gels" is adopted. Based on the steady-state friction test mode, when the load is 14 kPa, the sliding rate is 0.001 mm / s, and the ambient temperature is 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 3.4×10 -3 In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.15 MPa and the friction coefficient was 3.6×10 -2 .
[0103] Example 9
[0104] (1) adding 4.8 wt % of sodium carboxymethyl cellulose, a first polymer having a weight average molecular weight of 1,000,000 and a degree of substitution of 0.65, 6.0 wt % of polyvinyl alcohol, a second polymer having a degree of polymerization of 4,200 and a degree of alcoholysis of 90%, and 0.5 wt % of an imidazoline-type surfactant to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0105] (2) The stainless steel plate was immersed in a solution containing 13.5 mg / mL dopamine hydrochloride, 4 M Au 3+ The solution pH was adjusted to 10 and the immersion time was 8 h. Polydopamine / Au was deposited on the surface of the stainless steel plate.3+ Bridge layer to obtain substrate-PDA / Au 3+ , and then rinse the substrate-PDA / Au with deionized water 3+ Surface removal of uncrosslinked dopamine monomers and Au not complexed by the bridging layer 3+ ;
[0106] (3) The hydrogel coating mixed precursor solution in step (1) is dipped and pulled to cover the substrate-PDA / Au in step (2) 3+ On the surface, PDA and the polymer chains in the precursor solution of the hydrogel coating undergo non-covalent interactions, adhering the polymer chains to the substrate surface. 3+ Au in the bridging layer 3+ The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 8 h and the diffusion temperature is 37 °C. 3+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0107] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -10°C and the thawing temperature being 25°C, and the cycles are repeated 5 times. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then immersed for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0108] The water content of the double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this embodiment is 83.2%, and the compression modulus is 12.6 MPa. Using the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in the journal Journal of Physical Chemistry B (1999) Vol. 103, No. 29, pp. 6007-6014 "Friction of Gels.4.Friction on Charged Gels", based on the steady-state friction test mode, when the load is 14 kPa, the sliding rate is 0.001 mm / s, and the ambient temperature is 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 5.6×10 -3 In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.76 MPa and the friction coefficient was 9.6×10 -1 .
[0109] Example 10
[0110] (1) adding 5.0 wt % of a first polymer sodium carboxymethyl cellulose having a weight average molecular weight of 3,000,000 and a degree of substitution of 0.8, 5.0 wt % of a second polymer polyvinyl alcohol having a degree of polymerization of 4,800 and a degree of alcoholysis of 99%, and 0.1 wt % of a surfactant sodium dodecylbenzene sulfonate to deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution;
[0111] (2) The polypropylene plate was immersed in a solution containing 15 mg / mL dopamine hydrochloride, 5 M In 3+ The solution pH was adjusted to 11 and the immersion time was 5 h. Polydopamine / In 3+ Bridge layer to obtain substrate-PDA / In 3+ , and then rinse the substrate with deionized water -PDA / In 3+ Surface removal of uncrosslinked dopamine monomers and In that is not complexed by the bridging layer 3+ ;
[0112] (3) Spraying the hydrogel coating mixed precursor solution in step (1) onto the substrate-PDA / In in step (2) 3+ On the surface, PDA interacts non-covalently with the polymer chains in the precursor solution of the hydrogel coating, adhering the polymer chains to the substrate surface. 3+ In the bridge layer 3+ The bridging layer diffuses into the mixed precursor solution of the hydrogel coating. The diffusion time is 1 h and the diffusion temperature is 26 °C. 3+ Complex cross-linking to form a first physically cross-linked hydrogel network with gradient cross-linking, wherein the shape of the hydrogel coating is fixed by the first physically cross-linked network;
[0113] (4) The hydrogel coating containing the gradient cross-linked first physically cross-linked hydrogel network in step (3) is then subjected to cyclic freeze-thaw cycles, with the freezing temperature being -4°C and the thawing temperature being 40°C, and the cycle is repeated 6 times. The polyvinyl alcohol polymer bounded in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The coating is then soaked for about a week, during which the water is changed several times to remove free metal ions and to stabilize the size of the hydrogel, thereby obtaining the dual-network gradient polysaccharide-based self-lubricating hydrogel coating.
[0114] The water content of the double network gradient polysaccharide-based self-lubricating hydrogel coating prepared in this embodiment is 71.1%, and the compression modulus is 9.6 MPa. Through the rotational rheometer DHR-2 of TA Company of the United States, the gel friction test method described in "Friction of Gels.4.Friction on Charged Gels", based on the steady-state friction test mode, when the load is 14 kPa, the sliding rate is 0.001 mm / s, and the ambient temperature is 25°C, the friction coefficient of the double network gradient polysaccharide-based self-lubricating hydrogel coating on the glass surface is only 5.2×10 -3 In comparison, under the same preparation process, the compression modulus of the physically cross-linked pure polyvinyl alcohol hydrogel without the addition of the first polymer and surfactant was 0.45 MPa and the friction coefficient was 2.8×10 -2 .
Claims
1. A method for preparing a double-network gradient polysaccharide-based self-lubricating hydrogel coating, characterized in that: The following steps are involved: (1) adding a first polymer, a second polymer, and a surfactant into deionized water for dispersion, swelling, and stirring to obtain a uniform hydrogel coating mixed precursor solution, wherein the first polymer is sodium alginate or sodium carboxymethyl cellulose, and the second polymer is polyvinyl alcohol; In step (1), based on the mass of the hydrogel coating mixed precursor solution, the mass fraction of the first polymer is 1-5%, the mass fraction of the second polymer is 5-20%, the mass fraction of the surfactant is 0.1-8.0%, the mass ratio of the first polymer to the second polymer is 1:1-10, and the mass ratio of the surfactant to polyvinyl alcohol is 1:1-50; The degree of polymerization of the polyvinyl alcohol is 1,000 to 5,000, and the degree of alcoholysis is 85 to 99%; The weight average molecular weight of the sodium alginate is 30,000-250,000, and the ratio of β-D-mannuronic acid / α-L-guluronic acid is 0.5-1.5; the weight average molecular weight of the sodium carboxymethyl cellulose is 3,000-3,000,000, and the degree of substitution is 0.5-0.9; (2) Immersing the target modified material substrate in a Tris solution containing dopamine hydrochloride / polyvalent metal ions, depositing a polydopamine / polyvalent metal ion bridging layer on the surface of the target modified material substrate, and obtaining a substrate-PDA / M n+ Modified material, wherein PDA is polydopamine, M n+ For polyvalent metal ions, the substrate was rinsed with deionized water - PDA / M n+ The uncrosslinked dopamine monomers and the multivalent metal ions not complexed by the bridging layer are removed from the surface of the modified material; The concentration of dopamine hydrochloride in the Tris solution is 2 to 15 mg / mL, the pH of the Tris solution is 8 to 11, the molar concentration of the polyvalent metal ion in the Tris solution is 0.1 to 5 M, and the immersion time is 5 to 48 h; The polyvalent metal ion is Ni 2+ 、Co 2+ , Cu 2+ Cr 3+ 、Zn 2+ 、Cd 2+ , Mn 2+ Mg 2+ , Ca 2+ , Fe 3+ 、Al 3+ , Ga 3+ 、Au 3+ or In 3+ ; (3) Covering the hydrogel coating mixed precursor solution obtained in step (1) with the substrate-PDA / M obtained in step (2) n + The surface of the modified material is formed by the polymer chains in the mixed precursor solution of the hydrogel coating and the PDA adhering to the substrate-PDA / M through non-covalent bonds. n+ Modified material surface, M n+ Diffusion from the bridging layer into the mixed precursor solution of the hydrogel coating, complexation and crosslinking with the first polymer, to obtain a hydrogel coating of a gradient crosslinked first physical crosslinked hydrogel network; The diffusion temperature is 4 to 40°C and the time is 1 to 48 hours; (4) The hydrogel coating of the gradient cross-linked first physically cross-linked hydrogel network obtained in step (3) is subjected to cyclic freeze-thaw, and the polyvinyl alcohol bound in the gradient cross-linked first physically cross-linked hydrogel network forms a uniform second physically cross-linked hydrogel network. The free metal ions are removed by soaking until the hydrogel size is stable, thereby obtaining a double-network gradient polysaccharide-based self-lubricating hydrogel coating; the freezing temperature of the cyclic freeze-thaw is -50 to -4°C, the thawing temperature is 4 to 40°C, and the number of cycles is 2 to 6 times.
2. The preparation method according to claim 1, characterized in that: In step (4), the immersion condition is immersion in water for 1 to 3 weeks, during which the water is changed several times until a dimensionally stable equilibrium state of the hydrogel is reached.
3. A double-network gradient polysaccharide-based self-lubricating hydrogel coating prepared by the preparation method according to claim 1 or 2.
4. Use of the double-network gradient polysaccharide-based self-lubricating hydrogel coating according to claim 3 in the preparation of medical implant materials.
Citation Information
Patent Citations
Modification method for preparing high-hydrophilic coating by dopamine-induced sol-gel process
CN104150787A
Preparation method of ceramic artificial joint grinding pair
CN115400264A
Self-healing polyvinyl alcohol-alginate double-network gel and preparation method thereof
CN107254056A
Double-network gradient structure polysaccharide-based self-lubricating hydrogel and preparation method thereof
CN115725092A